Changes in plant life‐form, pollination syndrome and breeding system at a regional scale promoted by land use intensity. Issue 11 (20th July 2015) - Moser, Dietmar; Dullinger, Stefan; Mang, Thomas; Hülber, Karl; Essl, Franz; Frank, Thomas; Hulme, Philip E.; Grabherr, Georg; Pascher, Kathrin; Traveset, Anna
Abstract Aim Parallel declines in plant and insect pollinator diversity under land use intensification may occur as a result of both taxonomic groups responding similarly, but independently, to habitat change or as a consequence of interdependence as insect‐pollinated plants decline due to pollinator loss. Here, we explore the relative roles of independent and interdependent declines by comparing correlations of species richness and land use intensity for different functional groups of plants. Location Austria. Methods Generalized linear and generalized linear mixed models were used to analyse trends in species richness of plant functional groups sampled along a land use intensity gradient across 100 agricultural landscapes (=625 × 625 m each). Plants were classified according to their pollination syndrome, breeding system and life span. Species numbers were related to the site‐specific proportional area of semi‐natural habitats as an indicator of land use intensity. Results Overall, as the level of agricultural intensification increased the proportion of outcrossing plants declined and the proportion of self‐pollinating plants increased. However, while perennial plant species richness decreased under more intensive land use independently of pollination syndrome or breeding system, the richness of annuals only declined for outcrossing species requiring specialized insect pollinators but not for those pollinated by wind‐ or unspecialized insect pollinators. Main conclusion From these patterns we infer that land use intensification mainly drives plant species loss by excluding perennial species which suffer from the conversion of land to annually harvested crop fields. Hence, parallel declines in plant and insect richness largely result from a common response of perennials and pollinators to habitat change. Nevertheless, for annual plants with specialized pollinator requirements our data support a cascading effect of pollinator decline on species richness.